New Ion elastic scattering Beam Line of analytical complex at Iар NAS Ukraine - Drozdenko, A.A.; Duvanov, S.M.; Mordyk, S.N.; Storizhko, V.E. (Вопросы атомной науки и техники, 2008)
The paper presents a description of new Ion Backscattering Beam Line. Small-size electrostatic accelerator “Sokol” with a beam energy range of 0.2…2.0 MeV is used as an ion source. A detail of the Beam Line is using of magnetic spectrometer which allows to carry out precise (several nm) quantitative layer-by-layer non-destructive element analysis of solid composition and structure using Ion Elastic Scattering technique. Design of Backscattering Chamber allows realizing a full set of Ion Beam Analysis techniques. Proton and helium ion backscattering spectra are presented from the thin film samples. Simulated spectra fit well the experimental ones together. The last shows the analytical efficiency of Backscattering Beam Line.